Penerapan nilai-nilai karakter disiplin melalui ekstrakurikuler Pramuka siswa kelas v sekolah dasar - Dina Misbakhul Indi; Reza Rachmadtullah (Piramida Akademi, 2026)
Character education is an essential effort in shaping students to become individuals with good morals, particularly through strengthening the value of discipline. Schools play a strategic role in fostering students’ disciplinary character, one of which is through Scout extracurricular activities. This study aims to examine in depth the implementation of disciplinary character values through Scout extracurricular activities in fifth-grade elementary school students, along with the supporting and inhibiting factors. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, field notes, and documentation involving Scout instructors, fifth-grade classroom teachers, and fifth-grade students. The findings reveal that Scout extracurricular activities contribute to the implementation of disciplinary character through students’ compliance with rules, adherence to instructors’ directions, and responsibility in completing tasks. Supporting factors include cooperation among school members, instructors’ firmness, and adequate facilities and infrastructure. Meanwhile, inhibiting factors consist of differences in students’ motivation levels and limited activity time. The study concludes that Scout extracurricular activities are effective in fostering students’ disciplinary character when supported by consistent guidance and a conducive school environment.